AlN/GaN/AlN heterostructures grown on Si substrate by plasma-assisted MBE for MSM UV photodetector applications. (January 2015) - Mohd Yusoff, M.Z.; Mahyuddin, A.; Hassan, Z.; Abu Hassan, H.; Abdullah, M.J.; Rusop, M.; Mohammad, S.M.; Ahmed, Naser M.
Abstract: The AlN/GaN/AlN heterostructures were successfully grown on silicon substrate by plasma-assisted molecular beam epitaxy (MBE). High purity gallium (7N) and aluminum (6N5) were used to grow GaN and AlN, respectively. The structural and optical properties of the samples have been investigated by high-resolution X-ray diffraction (HR-XRD), photoluminescence (PL), Raman spectroscopy, transmission electron microscopy (TEM), selected area electron diffraction (SAED), dark field scanning transmission electron microscopy (DF STEM), and high-angle annular dark field scanning transmission electron microscopy (HAADF STEM). HR-XRD measurement showed that the sample has a typical diffraction pattern of hexagonal AlN/GaN/AlN heterostructures. Raman spectra revealed all four Raman-active modes, i.e., GaN-like E2 (H), AlN-like A1 (TO), AlN-like E2 (H), and AlN-like A1 (LO) inside the AlN/GaN/AlN heterostructures. Good thickness uniformity of the layers and high-quality hetero-structures without cracking were confirmed by TEM, SAED, DF STEM and HAADF STEM. The fabricated AlN/GaN/AlN heterostructures based metal-semiconductor-metal (MSM) for the UV photodetector shows a rise and fall of photoresponses, suggesting that the AlN/GaN/AlN heterostructures have good carrier transport and crystallinity properties.